Strong expression of EZH2 and accumulation of trimethylated H3K27 in diffuse large B-cell lymphoma independent of cell of origin and EZH2 codon 641 mutation. Issue 10 (3rd October 2015) - Zhou, Zheng; Gao, Juehua; Popovic, Relja; Wolniak, Kristy; Parimi, Vamsi; Winter, Jane N.; Licht, Jonathan D.; Chen, Yi-Hua
Abstract : Gain-of-function EZH2 mutation promotes H3K27 trimethylation (H3K27me3) and lymphoid transformation of germinal center (GC) derived B-cell lymphoma, such as GCB diffuse large B-cell lymphoma (DLBCL), but not activated B-cell (ABC) DLBCL. It is unclear whether expression levels of EZH2 and consequential H3K27me3 vary by EZH2 mutation and/or cell-of-origin in DLBCL. Ninety lymphoma samples including 40 DLBCLs were studied by immunohistochemistry. EZH2 Y641 mutations were detected in three of 20 (15%) GCB and none of 20 ABC types. All 40 DLBCLs showed strong EZH2, expression with high-level H3K27me3 in 90% GCBs and 95% ABCs. In 50 other B-cell lymphomas except for follicular lymphoma, strong EZH2 expression correlated with high-grade features. Immunoblot of DLBCL cell lines and microarray gene expression study of EZH2 in B-cell lymphomas were consistent with the immunohistochemistry findings. High-level EZH2 and H3K27me3 were common in DLBCL independent of cell-of-origin and EZH2 mutation. High-level EZH2 in lymphoma of aggressive features suggests additional therapeutic targets.